Best Answer

In the given expression you replace x by 2 and y by 1.

Thus 5xy + 7x2 - 12y = 5*x*y + 7*x2 - 12*y

= 5*2*1 + 7*22 - 12*1 = 10 + 28 - 12 = 26

Study guides

Q: How do you solve 5xy plus 7xsquared - 12y when x equals 2 y equals 1?

Write your answer...

Submit

Still have questions?

Related questions

12y - 4 = 7y + 165y = 20y = 4

-6x + 12y = -102 -6x = -12y - 102 x = 2y + 17

12y+2=146 12y=146-2 12y=144 144/12 12x12=144 y=12

12y = 132y = 132/12y = 11

12y + 5 = 53 12y = 48 y = 4

Answer:12y=132y=132/12=11

2x + 12 y =36subtract 2x from both sides12y = 36 - 2xdivide both sides by 12y = (36 - 2x)/12

5*3y+1+12y-1 = 15y+1+12y-1 = 27y.

The given equation: =3x-4x plus 9xy-12y =3x-4x+9xy-12y =-x+9xy-12y =-x+3y(3y-4) Answer.

12y+3=9y-15 3y=-18 y=-6

12y = 8x + 24 so y = 2x/3 + 2

6y + 4.. i think

People also asked

Featured Questions